2002
DOI: 10.3354/cr021165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of empirical relationships between indices of ENSO and NAO and agricultural yields in Spain

Abstract: This study characterizes the influence of the El Niño-Southern Oscillation (ENSO) and the North Atlantic Oscillation (NAO) on the most important crops in Spain using statistical analysis of the response of historical yields to ENSO and NAO phases. The response to ENSO phases is weak, being only significant for lemon yields, whereas the response to NAO phases is stronger, being significant for lemon, wheat, rye and olive. The results could be useful for producers, allowing them to adjust crop management, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
4
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 12 publications
1
33
4
1
Order By: Relevance
“…precipitable water, Toscano et al 2014) and indices (e.g. North Atlantic Oscillation and El Niño− Southern Oscillation, Gimeno et al 2002) defining similarity of weather patterns in the historical time series. Further, implementing different classification and selection techniques instead of the conventional Euclidean norm can be a way to improve skill in prediction (Akbari et al 2011, Crochet 2013.…”
Section: Resultsmentioning
confidence: 99%
“…precipitable water, Toscano et al 2014) and indices (e.g. North Atlantic Oscillation and El Niño− Southern Oscillation, Gimeno et al 2002) defining similarity of weather patterns in the historical time series. Further, implementing different classification and selection techniques instead of the conventional Euclidean norm can be a way to improve skill in prediction (Akbari et al 2011, Crochet 2013.…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of agricultural production variability on ENSO and its application to the forecasting of food production have been investigated in Africa, America, Europe, and South Asia (e.g. Cane et al 1994, Jones et al 2000, Orlove et al 2000, Ferreyra et al 2001, Gimeno et al 2002, Mavromatis et al 2002, Phillips et al 2002, Meza & Wilks 2003, Selvaraju 2003, but few such studies are available on EAM and ENSO in SE Asia or China. Our aims in this study were, to analyze for the major agricultural regions of China, (1) seasonal climate variability associated with EAM and ENSO and (2) the dependence of agricultural production on seasonal climate variability.…”
mentioning
confidence: 99%
“…Through its effects on weather conditions, the NAO also has an indirect influence on certain economic activities. Some studies have empirically demonstrated the influence of the NAO on the agricultural sector (Gimeno et al 2002, Kim & McCarl 2005, the energy sector (Cherry et al 2005), and marine transport (Woolf et al 2003). The influence of the NAO on the tourism sector has not previously been studied.…”
Section: Abstract: North Atlantic Oscillation · International Tourismentioning
confidence: 99%
“…The use of cross-correlation functions is the most common method of analysis applied in natural science research to detect connections between atmospheric variability described by the NAO index and different climatic, biological, and oceanographic variables (Hurrell 1995, Gimeno et al 2002, Orfila et al 2005, among many others). Nevertheless, this analysis should be handled with care since if each one of the analyzed series has a very high degree of autocorrelation, then the non-zero values of the cross-correlation function do not necessarily imply a true relationship between the 2 time series (Katz 1988).…”
Section: Cross-correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation